2014
DOI: 10.1109/rbme.2013.2294796
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Brain Interfaces

Abstract: Abstract-The brain is a large network of interconnected neurons where each cell functions as a nonlinear processing element. Unraveling the mysteries of information processing in the complex networks of the brain requires versatile neurostimulation and imaging techniques. Optogenetics is a new stimulation method which allows the activity of neurons to be modulated by light. For this purpose, the cell-types of interest are genetically targeted to produce light-sensitive proteins. Once these proteins are express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 228 publications
(301 reference statements)
0
64
0
Order By: Relevance
“…With the introduction of optogenetics [8,9] , a method that permits on-demand excitation and inhibition of activity in optically-sensitized neurons with light pulses, integration of photonic modules into microelectronic neural recording probes yielded closed-loop sensor-actuator devices [10] . These probes often combined optical fibers with established neural recording technologies such as silicon miltielectrode arrays [11,12] , multitrodes [13,14] and tetrodes [15] .…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of optogenetics [8,9] , a method that permits on-demand excitation and inhibition of activity in optically-sensitized neurons with light pulses, integration of photonic modules into microelectronic neural recording probes yielded closed-loop sensor-actuator devices [10] . These probes often combined optical fibers with established neural recording technologies such as silicon miltielectrode arrays [11,12] , multitrodes [13,14] and tetrodes [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Optogenetics involves the insertion of light-sensitive opsins into the cell membrane to infer optical excitation or inhibition in neural cells. 1,2 The most commonly used techniques involve the use of optically driven cationic channels (e.g., channelrhodopsin-2 (ChR2)) to excite activity and ionic pumps (e.g., halorhodopsin and archaerhodopsin) to inhibit neural activity. As a genetic technique, promotors can be used to express opsins in specific cell types.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to consider the position of an optical fiber as well as the direction of light delivery during optogenetic stimulation [19,20] or other neuroscience experiments. The measured data clearly showed that the expression of fluorescence protein can diffuse in different directions with respect to the fibers main lobe of radiation.…”
Section: Resultsmentioning
confidence: 99%